2015
DOI: 10.1590/s1516-89132015060278
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Quality and Testicular Histomorphometry of Wistar Rats Supplemented with Extract and Fractions of Fruit of Tribulus terrestris L.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
(23 reference statements)
1
11
0
2
Order By: Relevance
“…The average score of 50 tubules was used to determine the spermatogenic activities (Erdemir et al, 2014). The germinal epithelial height and the average diameter of the seminiferous tubules and its luminal diameter were taken according to the method described by Oliveira et al (2015).…”
Section: Histological Studiesmentioning
confidence: 99%
“…The average score of 50 tubules was used to determine the spermatogenic activities (Erdemir et al, 2014). The germinal epithelial height and the average diameter of the seminiferous tubules and its luminal diameter were taken according to the method described by Oliveira et al (2015).…”
Section: Histological Studiesmentioning
confidence: 99%
“…The hexanic and aqueous soluble fraction in the methanol fractions promoted changes in the intertubular compartment because they increased the nuclear volume, cytoplasmic volume and individual volume of Leydig cells in male Wistar rats [57]. …”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In the literature, it has been concluded that the ethanol extract of T. terrestris (EETT) influences spermatogenesis, as shown by the evident changes in the tubular compartment of the testes, such as increases in the total tube length, tubular volume and height of the seminiferous epithelium. The hexanic and aqueous soluble fraction in the methanol fractions promoted changes in the intertubular compartment because they increased the nuclear volume, cytoplasmic volume and individual volume of Leydig cells in male Wistar rats [ 57 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Os resultados demonstraram que o extrato etanólico de T. terrestris (EETT) influencia a espermatogênese pelas evidentes alterações no compartimento tubular dos testículos, como aumentos no comprimento total do tubo, volume tubular e altura de o epitélio seminífero. A fração solúvel hexânica e aquosa nas frações de metanol promoveram alterações no compartimento intertubular, pois aumentaram o volume nuclear, o volume citoplasmático e o volume individual das células de Leydig em ratos Wistar machos (Oliveira et al, 2015).…”
Section: Habituais Usos Farmacológicos Do Tribulus Terrestrisunclassified